Christmas Gifts Exchange between Parents and Children as a Nonverbal Means of Communicating Care - Latinytė, Rūta (Tautosakos darbai, 2021)
The article focuses on the Christmas gifts that parents give to their children and afterwards – that the grown-up children in turn give to their parents and their own kids, as remembered and described by the informants in the course of unstructured interviews. The subject of analysis comprises memories and narratives of the respondents, including a description of personal experience by the author. The choice of the Christmas is anything but accidental, since this period is characterized as the most intense gift-giving time, according to various opinion polls both in Lithuania and in other countries. Studies of everyday practices applied in the phenomenological anthropology allow viewing this popular practice through personal narratives. Analysis of the individual experience stories reveals modes of establishing special relationship between the gift giver and the receiver against the background of the season’s holidays. Sleep is noted to be an important element in the process of creating this relationship, since sleep is a form of existential death, which in a way guarantees longevity of the social bonds. In the course of years, when individual ceases to be a child in relation to people around him/her, and becomes a grown-up instead, an inversion of roles between the giver and the receiver takes place, which, however, is asymmetrical: the obligation to repay the received gifts directs the gift giving intention towards the future generations. The study reveals yet another aspect of these interactions: namely, the gift, as a nonverbal means of communication, enables mutual understanding between family members that is reached without any words, just by an experienced knowledge, which is defined as a lived experience in phenomenology.